(untitled) (UUM Journal of Legal Studies, 2025)
The misclassification of platform workers as independent contractors has sparked extensive debates globally, with notable implications for employment protections. In Malaysia, the classification of platform workers, as exemplified in Loh Guet Ching v Menteri Sumber Manusia & Anor case, remains a contentious issue. Despite the Court of Appeal’s ruling, Section 101C of the Employment Act 1955, in force since 1st January 2023, introduces a mechanism to ascertain employment status. This provision, untested as of yet, presents a potential resolution for misclassification disputes involving platform workers. This article delves into the current employment legal landscape in Malaysia, exploring recent developments and potential solutions for resolving the misclassification dilemma. Utilising a doctrinal approach, the study analyses both legal and non-legal sources, revealing that selected jurisdictions have adeptly addressed misclassification challenges. Common law tests, which are prevalent in judicial proceedings, and the purposive approach offer avenues for resolution, while statutory tests, though providing clarity, require careful application due to potential adverse consequences.